2015
DOI: 10.4236/ojn.2015.56056
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Sleep at the Ward after Cardiothoracic Surgery

Abstract: Objective: Sleeping problems are among the issues most mentioned by patients after cardiothoracic surgery. These problems can have a negative effect on duration of the hospital stay and recovery. In the ward of our cardiothoracic surgery department, a study was initiated to assess the quality of sleep after cardiothoracic surgery. The primary objective was to investigate the effect of cardiothoracic surgery on the quality of sleep. The secondary objective was to investigate the quality of sleep. Correlations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Studies show that over 80% of adults, 30 years and older, had sleep disruptions during the first week after cardiac surgery. In these studies, nearly 70% of adults who had coronary artery bypass and/or heart valve surgery continued to be sleep deprived up to 6 months after hospitalisation (Liao, Huang, Huang, & Hwang, ; Propper, van Domburg, Brunott, & Bogers, ; Yang, Huang, Tsai, & Lou, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that over 80% of adults, 30 years and older, had sleep disruptions during the first week after cardiac surgery. In these studies, nearly 70% of adults who had coronary artery bypass and/or heart valve surgery continued to be sleep deprived up to 6 months after hospitalisation (Liao, Huang, Huang, & Hwang, ; Propper, van Domburg, Brunott, & Bogers, ; Yang, Huang, Tsai, & Lou, ).…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac surgery, sleep disruption is characterised by the patient's inability to initiate and maintain sleep (Liao et al., ; Propper et al., ; Yang et al., ). Sleep disruption is a multidimensional phenomenon stimulated by a myriad of factors including, but not limited to, pain, anxiety, stress and inflammatory response postcardiopulmonary bypass (Casida, Davis, Shpakoff, & Yarandi, ; Casida & Nowak, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the overall PSQI score, it was shown that 61.7% of patients in the preoperative period at home slept poorly. Propper et al [21] report that among patients after thoracic surgery, their sleep quality one month after surgery was lower than before the surgery. However, this work noted that the overall PSQI score may differ from the subjective assessment of sleep quality indicated by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that poor sleep quality was associated with higher fatigue levels in patients with valvular heart disease and coronary angiography pre‐surgery (Lakshmanan et al, 2021; Onegi & Arslan, 2021). A cohort study found that patients reported poorer sleep quality after cardiothoracic surgery than before surgery due to pain or disturbance from medical devices, and the quality of sleep one month after surgery was also worse than before surgery (Pröpper et al, 2015). Therefore, nurses should also assess sleep quality in patients undergoing cardiac surgery and provide appropriate interventions, such as education on sleep hygiene, to improve their sleep quality during different recovery periods.…”
Section: Discussionmentioning
confidence: 99%